Fiscal Sustainability in Developing Asia - Charles Adams; Benno Ferrarini; Donghyun Park (Asian Development Bank (ADB), 2010)
The central objective of this paper is to empirically examine the issue of fiscal sustainability in developing Asia. To do so, we first diagnose the region's public finances by analyzing the evolution of key fiscal indicators over time and across subregions. We then estimate fiscal policy response functions that measure the adjustment of the primary fiscal balance to public debt positions. Overall, our results indicate that the region's public finances are in good shape as a result of responsible fiscal behavior. Nevertheless, failure to withdraw the region's anticrisis fiscal stimulus in a timely manner may jeopardize fiscal sustainability, bolstering the case for strong medium-term fiscal policy frameworks.
hdl:11540/1949
Keywords: E62; H62; H63; 330; Fiscal sustainability; Asia; fiscal policy; fiscal balance; public debt; Finanzkrise; Finanzmarktregulierung; Antizyklische Finanzpolitik; Wirkungsanalyse; Asien